Soluble fibres modulate dough rheology and gluten structure via hydrogen bond density and Flory-Huggins water interaction parameter - Stefano Renzetti; Lisa Lambertini; Helene C.M. Mocking-Bode; Ruud G.M. van der Sman (Current Research in Food Science)
Soluble fibres are gaining increasing interest for functional food applications like bread, but their interaction with gluten and effects on dough rheology are not fully elucidated. This study hypothesized that soluble fibres influence gluten structure and dough rheology by acting as plasticizers and humectants. Plasticizing properties depend on the effective number of hydrogen bonding sites available in the fibre molecule (NOH,s). Humectant properties are related to the water interaction parameter derived from analysis of the sorption behaviour. Oligo-fructoses, inulins, polydextrose and a glucose syrup were added individually and in mixtures to wheat dough to test the hypothesis. PCA and multi-linear regressions showed that the G′ from temperature sweeps increased with an increase in the effective volume fraction of hydrogen bonding sites (Φw,eff) in the solvent and in the water interaction parameter (χeff). The enhanced G′ corresponded to a reduction in tan(δ), indicating an increased elastic behaviour. The parameters Φw,eff and χeff also explained the changes in phase transitions during heating, i.e. Tonset and Tpeak of starch gelatinization (R2 > 0.9). Image analysis of the gluten network revealed that fibre structure and physico-chemical properties influenced the gluten network by altering branching rate, lacunarity, and protein strand width. Comparing inulins and polydextrose of similar molecular weights (Mw) indicated that interactions with gluten were influenced more by NOH,s than Mw. High Mw inulins, with a linear structure, promoted junctions in the gluten network through hydrogen bonds, and possibly phase separation in gluten-rich and inulin-rich phases. In contrast, the more hydrophilic, branched polydextrose reduced junction formation in the gluten network due to fewer NOH,s. This study provides new insights into the physico-chemical properties of soluble fibres and their role in wheat dough functionality.